High-sensitive cardiac troponin T as a marker of hemorrhagic complications in elderly patients anticoagulated for non-massive pulmonary embolism. Issue 185 (January 2020) - Simona, Aurélien; Limacher, Andreas; Méan, Marie; Golaz, Olivier; Bounameaux, Henri; Aujesky, Drahomir; Righini, Marc; Vuilleumier, Nicolas
Abstract: Background: Recent data have raised concerns about the risk/benefit ratio of thrombolysis in non-high risk pulmonary embolism patients due to increased serious bleeding events. Whether cardiac biomarkers could be of help for bleeding risk stratification in this setting remains elusive. Objectives: To determine the prognostic accuracy of hs-cTnT, NT-proBNP, RIETE and PESI score for the occurrence of clinically relevant bleeding (CRB) in elderly patients under conventional anticoagulation therapy for non-massive pulmonary embolism (NMPE). Methods: We evaluated 230 elderly patients with available blood sample taken within one day from diagnosis. The primary study endpoint was CRB at 1, 3 and 24 months. Prognostic accuracies and associations were determined using C-statistics and subhazard ratios (SHR), respectively. Results: hs-cTnT displayed the highest discriminatory power at 1 month (C-statistics: 0.77, 95% CI: 0.68–0.88) which remained stable over time. Although C-statistics comparison indicated that hs-cTnT was not statistically superior to RIETE score (0.77 vs 0.67, p = 0.11), adding hs-cTnT to RIETE score significantly improved the C-statistics from 0.67 to 0.78 ( p = 0.02). SHRs indicated that for each hs-cTnT log-unit increase, there was a 58% increase in the risk of CRB independently of the RIETE score (adjusted SHR: 1.58, 95% CI: 1.31–1.92). At the pre-specified cut-off of 14 ng/l, the negative predictive value of hs-cTnT was 96.9% (95% CI: 91.4–99.0) and 94.9 (95%CI: 88.6–97.8) at 1 and 3 months, respectively. Conclusion: In elderly, hs-cTnT provides incremental prognostic information over the RIETE score and could represent a valuable tool to identify NMPE patients at low risk of bleeding. Highlights: High cardiac biomarkers levels predict poor prognosis in pulmonary embolism (PE). hs-cTnT independently predicts short/long-term haemorrhagic complications in PE. hs-cTnT provides added value to the RIETE score for haemorrhages prediction in PE.